An analytical algorithm for the pylon saddle pushing stage and distance during the suspension bridge construction. Issue 15 (November 2019) - Zhang, Wen-ming; Qian, Kai-rui; Tian, Gen-min; Liu, Zhao
During the construction of suspension bridges, the stress state of the pylon (tower) is improved by pushing the pylon saddle by an appropriate distance at the proper time. An analytical algorithm for the assessment of the required timing and displacements for the pylon saddle pushing at particular construction stages is proposed and verified in this study. The timing calculation is based on the assessment of current hanger tensile forces at each construction stage and the pylon stress state, while the pushing distance/displacement is derived from the conditions of elevation difference closure and the conservation of unstrained length of the main cable segments. This algorithm was successfully applied during the construction of a particular suspension bridge in China with a main span of 730 m. The results obtained strongly indicate that the bending moment in the pylon bottom is contributed by both horizontal and vertical forces of the main cable. The horizontal constituent is dominant and its share gradually increases in the bridge construction process. In a suspension bridge with side spans of various lengths, the stresses in the pylon bottom on the side with a larger side span is more likely to exceed the limit. Therefore, the respective strength criterion controls the pylon saddle-pushing schedule. The proposed analytical algorithm is quite straightforward and is recommended for wider application.